2020
DOI: 10.3389/fpls.2020.01156
|View full text |Cite
|
Sign up to set email alerts
|

KatE From the Bacterial Plant Pathogen Ralstonia solanacearum Is a Monofunctional Catalase Controlled by HrpG That Plays a Major Role in Bacterial Survival to Hydrogen Peroxide

Abstract: plant tomato is also studied, revealing that disruption of this gene has no effect on R. solanacearum virulence or bacterial growth in leave tissues, which suggests a minor role for this catalase in bacterial fitness in planta. Our work provides the first characterization of the R. solanacearum catalases and identifies KatE as a bona fide monofunctional catalase with an important role in bacterial protection against oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
(81 reference statements)
1
11
0
Order By: Relevance
“…The ability of bacterial survival above and inside the host relies on its capacity to counteract ROS generation/scavenging (Leonard et al, 2017). In Xaj, we observed a differential expression pattern of the enzymatic antioxidant system during the abiotic stress test, suggesting that oxidative stress response genes are regulated by external conditions, as demonstrated in other plant‐pathogenic bacteria (Tondo et al, 2020).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The ability of bacterial survival above and inside the host relies on its capacity to counteract ROS generation/scavenging (Leonard et al, 2017). In Xaj, we observed a differential expression pattern of the enzymatic antioxidant system during the abiotic stress test, suggesting that oxidative stress response genes are regulated by external conditions, as demonstrated in other plant‐pathogenic bacteria (Tondo et al, 2020).…”
Section: Discussionsupporting
confidence: 63%
“…The expression levels of three target genes ( cat , sod , and gpx ) encoding ROS‐scavenging enzymes involved in ROS detoxification were evaluated using selected RGs as normalization factors. Bacteria are exposed to ROS produced during aerobic respiration and subsequent extracellular/environmental interactions (Tondo et al, 2020). Several studies have demonstrated that the antioxidant enzymatic system in phytopathogen bacteria is involved in overcoming oxidative plant defence during host colonization (Cabrejos et al, 2019; Leonard et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, pathogens also secret CAT to interfere with plant host immune responses. For example, KatE, a single monofunctional CAT secreted by Ralstonia solanacearum , plays essential roles in bacterial survival under oxidative stress conditions (Tondo et al ., 2020). Similarly, Blumeria graminis , an obligate biotrophic fungal pathogen of barley, secrets an extracellular CAT, which contributes to its pathogenicity during infection and suppresses the host defence (Zhang et al ., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…tomato T1 ( Chowdhury and Jagannadham, 2013 ), whereas CAT was detected in the OMVs of Xanthomonas citri subsp. citri and Ralstonia solanacearum ( Tondo et al, 2016 , 2020 ). The presence of oxidative enzymes in the OMVs of other Xanthomonadaceae and Burkholderiaceae causing widespread damage in crop production requires further elucidation ( Sidhu et al, 2008 ; Sousa et al, 2020 ).…”
Section: Outer Membrane Vesicles As a Versatile Tool In Bacteria–bact...mentioning
confidence: 99%